2019
DOI: 10.1371/journal.pone.0223570
|View full text |Cite
|
Sign up to set email alerts
|

Sex affects immunolabeling for histone 3 K27me3 in the trophectoderm of the bovine blastocyst but not labeling for histone 3 K18ac

Abstract: The mammalian embryo displays sexual dimorphism in the preimplantation period. Moreover, competence of the embryo to develop is dependent on the sire from which the embryo is derived and can be modified by embryokines produced by the endometrium such as colony stimulating factor 2 (CSF2). The preimplantation period is characterized by large changes in epigenetic modifications of DNA and histones. It is possible, therefore, that effects of sex, sire, and embryo regulatory molecules are mediated by changes in ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The X-chromosome bias of the SDMT and identification of factors related with DNA methylation machinery, reproduction, meiotic cell cycle and gamete generation strengthens the link between sexual transcriptomic and epigenetic dimorphism in blastocysts. Moreover, other epigenetic marks such as histone modifications have revealed epigenetic dimorphism recently, as it can be modified in the trophoctoderm by embryo sex [71]. Furthermore, there are other organisms in nature, as aphids, which in the absence of confounding genetic variation, have revealed that methylation regulates phenotypic plasticity and is intrinsically linked to sexual dimorphism [72].…”
Section: Discussionmentioning
confidence: 99%
“…The X-chromosome bias of the SDMT and identification of factors related with DNA methylation machinery, reproduction, meiotic cell cycle and gamete generation strengthens the link between sexual transcriptomic and epigenetic dimorphism in blastocysts. Moreover, other epigenetic marks such as histone modifications have revealed epigenetic dimorphism recently, as it can be modified in the trophoctoderm by embryo sex [71]. Furthermore, there are other organisms in nature, as aphids, which in the absence of confounding genetic variation, have revealed that methylation regulates phenotypic plasticity and is intrinsically linked to sexual dimorphism [72].…”
Section: Discussionmentioning
confidence: 99%
“…Another important determinant of the function of the preimplantation embryo is embryo sex. In cattle, for example, male blastocysts differ from females in terms of gene expression, mitochondrial DNA content, telomere length, DNA methylation, histone methylation and secretion of the signaling molecule, interferon-τ ( Siqueira and Hansen 2016 ; Bermejo-Alvarez et al 2010 ; Bermejo-Alvarez et al 2008 ; Larson et al 2001 ; Carvalheira et al 2019 ). Female embryos have been reported to develop slower, undergo more apoptosis and have lower cell number than male embryos ( Ghys et al 2015 ; Oliveira et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%